We are working on it. The debates that emerged facing the update of the Comprehensive Sexual Education law in 2018 (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
In 2006, Néstor Kirchner’s government passed Law No. 26,150 “Programa Nacional de Educación Sexual Integral (ESI)” (National Comprehensive Sex Education Program). This law was innovative, as its approach broadened the responsibilities of Sexual Education, and included an issue in an explicitly public agenda that until then seemed confined to the private sphere: sexuality.Currently we find ourselves in a neoliberal context, understood as a particular type of society that denotes a criticism of the discourses of equality, justice and democracy, and seeks to trivialize the public sphere, favoring a privatization tendency, legitimizing the hegemony of the market (Giroux, 2015). We are interested in observing how this process affects the transmission of knowledge about sexuality. We will focus on how this transmission’s methods, contents and places are strained since the questioning of the Comprehensive Sexual Education Law that emerged in 2018, after the intention of revising the law for its update, in the context of the debate on the Voluntary Interruption of Pregnancy law. Within this framework, groups emerged in the public debate (fundamentally disputing on social networks) that strongly opposed the law and its modification.
Keywords: Comprehensive Sex Education; Sexuality; State; Neoliberalism; social networks